Exposição parental transitória à metionina : avaliação de parâmetros comportamentais e neuroquímicos em pais e prole de zebrafish - Zanandrea, Rodrigo (2020)
Methionine participates directly or indirectly in the formation of other amino acids, neurotransmitters and in methylation processes, ensuring the homeostasis of an organism. However, genetic causes, called innate metabolism errors, or non-genetic causes can increase plasma methionine levels, a condition known as hypermethioninemia. Consequently, myopathies, liver disease and neurological problems can arise, and even a transient increase can cause toxicological effects. In addition, given the role of methionine in epigenetic control processes, subsequent generation may also be affected. However, assessments of the effects of transient hypermethioninemia are scarce and the mechanisms underlying this pathology have not yet been explored. Thus, the aim of this study was to explore the effects of transient hypermethioninemia in zebrafish parents and their offspring. Morphological changes, heartbeat, survival and locomotion were evaluated in the offspring in the larval stage, while anxiety, aggression, social interaction and aversive memory were evaluated in the parents and in the offspring in the adult stage. The levels of neurotransmitters and amino acids and the oxidative profile have also been explored in parents exposed to methionine and their offspring. The results obtained demonstrate that an exposure to methionine has long-lasting neurotoxic effects, since after the removal of methionine the exposed animals showed a decrease in anxiety, a decrease in aggression, and memory deficits. Concomitant to this, the levels of carnitine, creatine, cysteine and epinephrine were altered and redox homeostasis impaired seen by decreased levels of catalase, superoxide dismutase and total thiol content. We also observed that a transient increase in methionine has transgenerational effects, since the offspring of the exposed parents was hyperactive in the larval stage and, in the adult stage, also showed a decrease in anxiety with increased levels of neurotransmitters and an altered oxidative profile with increase of DCF levels. Therefore, high levels of methionine, even if transient, can cause long-lasting behavioral and neurochemical changes with effects also observed in the subsequent generation.